1997
DOI: 10.1111/j.1465-7295.1997.tb02033.x
|View full text |Cite
|
Sign up to set email alerts
|

Voting Behavior, Discrimination and the National Baseball Hall of Fame

Abstract: We investigate whether black, Latin, and white major league baseball players receive the same consideration by the Baseball Writers ' Association of America in voting for membership into The National Baseball Hall of Fame. The first stageof Heckman b two-step procedure indicates that the probability a black player will ever receive at least one vote is significantly lower than that for his white counterpart. The second stage suggests that race or ethnicity sometimes matter in determining the number of votes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 10 publications
0
31
1
Order By: Relevance
“…This research adds to a large literature on racial discrimination in sports, specifically in baseball, going back at least to Pascal and Rapping (1972) and Gwartney and Haworth (1974), with more recent examples being Nardinelli and Simon (1990), Findlay and Reid (1997) and Bradbury (2007). It includes studies of such outcomes as productivity, wages, customers' approbation of players, selection for honors, and others.…”
Section: Introductionmentioning
confidence: 99%
“…This research adds to a large literature on racial discrimination in sports, specifically in baseball, going back at least to Pascal and Rapping (1972) and Gwartney and Haworth (1974), with more recent examples being Nardinelli and Simon (1990), Findlay and Reid (1997) and Bradbury (2007). It includes studies of such outcomes as productivity, wages, customers' approbation of players, selection for honors, and others.…”
Section: Introductionmentioning
confidence: 99%
“…The elite card positions are (theoretically) reserved for the elite players and this is precisely the relationship being tested. While some research has indicated racial bias in election to the Pro Baseball HOF (for example Desser et al 1999;Findlay and Reid 1997), our sample includes not only those elected to the Pro Football HOF, but also those appearing on the finalist's roster and this inclusion should aid in mitigating bias if it indeed exists. 6 Another dependent variable was created and tested: the ratio of card points to number of appearances.…”
Section: The Samplementioning
confidence: 99%
“…-Peter Gammons (Gammons and Stark, 2007) Past research of modeling MLB's HOF membership typically investigated if racial discrimination existed among voters (Jewell, 2003) (Findlay and Reid, 1997) (Desser, et al, 1999). These studies support that the presence of racial discrimination does not appear to be significant.…”
Section: Introductionmentioning
confidence: 98%